2016
DOI: 10.1111/jvim.13929
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Course of Biliary Sludge Over 12 Months in Dogs with Ultrasonographically Identified Biliary Sludge

Abstract: BackgroundBiliary sludge is associated with gallbladder (GB) dysmotility and mucus hypersecretion suggesting a link between biliary sludge and the formation of GB mucoceles (GBM). If biliary sludge progresses to GBM, treatment to reduce the production and progression of sludge is warranted.Hypothesis/ObjectivesThe objective of this study was to determine the course of biliary sludge in dogs.AnimalsSeventy‐seven healthy, client‐owned dogs ≥4 years of age screened for biliary sludge; 45 affected dogs identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…Gravity‐dependent biliary sludge has been observed to progress to NDBS (DeMonaco et al . 2016) and it is possible that gall bladder dysmotility and cholecystitis are more important for the progression of gravity‐dependent biliary sludge to NDBS than cystic mucosal hyperplasia in dogs. Based on the literature search, similar progression from NDBS to GBM has not been reported although it has been speculated that the formation of NDBS precedes GBM formation (Tsukagoshi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gravity‐dependent biliary sludge has been observed to progress to NDBS (DeMonaco et al . 2016) and it is possible that gall bladder dysmotility and cholecystitis are more important for the progression of gravity‐dependent biliary sludge to NDBS than cystic mucosal hyperplasia in dogs. Based on the literature search, similar progression from NDBS to GBM has not been reported although it has been speculated that the formation of NDBS precedes GBM formation (Tsukagoshi et al .…”
Section: Discussionmentioning
confidence: 99%
“…2014, DeMonaco et al . 2016). At the stage of disease reported in this study, in which a mixed pattern of anechoic bile and NDBS was present on ultrasonogram, the dogs could not be described to have GBM based on histological evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Supersaturation of bile with cholesterol has been associated with impaired gallbladder motility in people and sludge formation in dogs and thus, may be a precursor to GBM formation. However, gall bladder sludge, while prevalent in older dogs, has not been shown to progress toward significant biliary disease over the course of a year and might not represent a risk factor in its own right. A recent study into the mechanisms of GBM formation identified a disproportionate increase in the gel‐forming mucin Muc5ac relative to Muc5b, defective mucin un‐packaging and altered levels of mucin‐interacting proteins as potential contributory factors .…”
Section: Discussionmentioning
confidence: 99%
“…, DeMonaco et al . ). Signs commonly reported with septic cholecystitis and cholangitis/cholangiohepatitis are symmetric or asymmetric gall bladder wall thickening, dilated common bile duct, double‐layered wall, hyperechoic wall, hyperechoic gall bladder contents and choleliths (Hittmair et al .…”
Section: Introductionmentioning
confidence: 97%